TEKNOLOGI ZONE AGROEKOLOGI DALAM PEMBANGUNAN PERTANIAN BERWAWASAN LINGKUNGAN - I Made Adnyana (Bumi Lestari Journal of Environment)
Technology of agroecologycal zonning is a land evaluation to using specific areaespecially in agriculture with friendly environment. Agroecologycal zonning based onfisically environment elements i.e., climate, physiography and landform, soil resources,vegetation and land use. Alternative commodities that will be devolloped based on socialeconomy factors. In area with stable land using (East and centre of Buleleng) thecommodities that will be choised : adaptive, profitable, and acceptability. In area with not yetstable land using (west of Buleleng) will be purposed with agroecologycal zonning as (1) atslopping area for suitable and profitable annual cropping, (2) at hilly area for multiplecropping, (3) in mountainous area with slope < 40% for multiple cropping and estate,whereas, if slope >40% and elevation >700 m over the sea level for plants conservation.